El peruano Juan Gargurevich, en la avanzada de los estudios teóricos e históricos sobre periodismo - Cantavella Blasco, Juan (Estudios sobre el Mensaje Periodístico, 2010)
For almost 40 years (after a long period working as a journalist) the Peruvian professor Juan GARGUREVICH has dedicated to his lectures on journalism, developed into classroms and books writing. Many articles and essays were fruit of his research in the field of Journalistic style, making an historical and contemporary approach to peruvian journalism. This academic labour was recognized not only in Perú, but also in other sudamerican countries. This scientific and critical view also appears in new books and trade union activities. Nowadays, he’s the director of “Club de Periodistas del Perú” (Peruvian Journalists Union).
Keywords: Press; Journalists; History of Peruvian Journalism; Journalistic style